PERLINDUNGAN HUKUM BAGI PENYIDIK POLRI DALAM PENGUNGKAPAN TINDAK PIDANA NARKOTIKA DENGAN MENGGUNAKAN TEKNIK PEMBELIAN TERSELUBUNG - Kumbul Kusdwidjanto Sudjadi; Surajiman (INTELIGENSIA MEDIA, 2022)
In disclosing narcotics crime cases, Polri investigators have various techniques and one of them is to carry out investigative actions with the technique of buying narcotics in disguise (undercover buy). This is also regulated in Article 75 letter (j) of Law Number 35 of 2009 concerning narcotics which states that in the context of conducting an investigation, investigators are given the authority to carry out covert purchase investigation techniques and delivery under supervision. This covert buying technique allows investigators to directly enter the narcotics distribution network and investigators can play a role as part of the narcotics distribution network. In practice, this hidden buying technique must be done carefully, because it is risky and can endanger the life safety of investigators who go undercover, and even threaten their families. The approach used in this study is an empirical juridical approach. The data used are secondary data and primary data. All data and materials obtained from the research results were compiled and analyzed qualitatively, and presented in a qualitative descriptive form. From the results of the research and discussion, it was concluded that Polri investigators in carrying out covert purchasing techniques in an effort to eradicate narcotics crimes basically received legal protection from the state through the provisions contained in Law Number 35 of 2009 concerning Narcotics. In addition, protection for the implementation of covert purchasing techniques is also basically protected by Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP) and Law Number 2 of 2002 concerning the Indonesian National Police. In the implementation of covert purchasing techniques for the disclosure of narcotics crime cases, of course it is not easy and many obstacles and obstacles are faced, both internally and externally. Internally, starting from the inadequate capabilities and skills of human resources, budget support is not fully supported, facilities and infrastructure are not supported, to the methods used in the implementation of covert purchases are not carried out optimally and leaks often occur. Meanwhile externally, such as the existence of legal regulations that require arresting witnesses, in this case Polri investigators, to be present at court hearings, community participation that is pessimistic, ignorant, does not dare to report, there is terror against the families of Polri investigators and also leaks in the implementation of activities due to networks and support. a stronger budget for narcotics crime network syndicates in Indonesia.